MANAGING RISK FOR SUCCESS IN A SOUTH AFRICAN ENGINEERING AND CONSTRUCTION PROJECT ENVIRONMENT - Chihuri, S.; Pretorius, L. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The role that project risk management plays in ensuring the successful delivery of engineering and construction projects in South Africa is addressed in this paper. A survey questionnaire was developed to establish approaches used for risk management, and tools and techniques for risk identification. The findings revealed that project risk management had a significant role to play in the success of projects in South Africa. Respondents whose organisations practised structured risk management processes reported success in their projects. The main challenge was found to be in the implementation of risk management tools and techniques. Thus it became apparent that widespread adoption of project risk management in South Africa seemed to be impeded by a low knowledge and skills base, especially in terms of its application. AFRIKAANSE OPSOMMING: Die rol wat projekrisikobestuur in die suksesvolle aflewering van ingenieurs- en konstruksieprojekte in Suid-Afrika speel word hier aangespreek.